Preliminary study of physical activity and physical activity behaviour among undergraduates of a private university - Wee, Eng Hoe; Singh, Tarsame Singh Masa; Anthony Dass, Anita Christina (Faculty of Sports Science and Recreation, 2025)
This study investigated the physical activity pattern and level among undergraduates. A total of 100 students (Male=29, Female=71) from a private university were conveniently chosen for this survey. Type of physical activity was measured by dichotomous items. Physical activity level (PAL) was measured using Physical Activity Index (Griffin, 2006). Results showed that most popular physical activity was exercise activities with females dominating in exercise activities, individual sport, team sport, outdoor leisure, and outdoor challenges as compared to males. In terms of PAL, majority of the participants was in the need improvement level (55%), with only 9% in the good and excellent level. Most participants have friends as their exercise partners, about 30% exercised with family members while about 46% preferred to exercise alone. Even though undergraduates of this study involved in a variety of physical activity, their physical activity level has left much to be desired.